Pengaruh Permainan Bola Voli Mini terhadap Tingkat Kebugaran Jasmani Siswa Sekolah Dasar - Asya, Siti Syarokah Annur; Sudirjo, Encep; Dinangsit, Dinar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to improve physical fitness through playing volleyball at SDN Simpang Baru. This research uses a quantitative method with experimental research, using a pre-experimental one-group pre-test post-test design. The instrument used in this research is the Indonesian physical fitness test for ages 10-12 years, which consists of 5 tests: body lift; sit-ups;vertical jump; 600 m medium distance run; 40 m sprint. The population in this study was students of SDN Simpang Baru class V, totaling 41 people. The sampling technique used was purposive sampling. Purposive sampling is a sample determination technique with specific considerations. The criteria for sampling are as follows: Simpang Baru Elementary School student attended during PJOK lessons, had no history of illness, and was 12 years old. After selecting based on the criteria, 37 samples were obtained. The data were analyzed using normality, homogeneity, and t-tests. The analysis results found that mini volleyball significantly influenced students' physical fitness, with a significance value of 0.000 <0.05. In conclusion, there is an influence of mini volleyball games on the physical fitness level of elementary school students Keywords: mini volleyball, physical fitness